Analysis of the Influence of Work Discipline, Job Training and Work Facilities on Employee Performance Through Job Satisfaction as an Intervening Variablein the Population and Civil Registration OfficeAsahan Regency - Yusmaida Panjaitan; Yohny Anwar; Muhammad Toyib Daulay (Equivalent : Journal of Economic, Accounting and Management, 2026)
This study aims to analyze the influence of work discipline, job training, and work facilities on employee performance with job satisfaction as an intervening variable at the Asahan Regency Population and Civil Registration Office. The research problem focuses on the varying levels of employee performance which are allegedly influenced by discipline, quality of training, and the availability of supporting facilities. This study uses a quantitative approach with a survey method through the distribution of questionnaires to employees. The data was analyzed using the Structural Equation Modeling (SEM) model to see the direct and indirect relationships between variables. The results of the study show that work discipline, job training, and work facilities have a positive and significant effect on employee performance, both directly and through job satisfaction. In addition, job satisfaction has been proven to play a role as an intervening variable that strengthens the influence of these three variables on employee performance. These findings emphasize the importance of improving discipline, training quality, and improving work facilities to encourage optimal performance of employees in government agencies.